Study of winding vibration and transmission characteristics of three-phase oil-immersed distribution transformer based on FEA. (August 2020) - Wu, X W; Zhang, Z Z; Zhu, L Y
Abstract: In this paper, the magnetic-structure-acoustic multi-physical field model of S13-M400/10 distribution transformer is established through the FEA software. The harmonic response analysis method is used to study the winding vibration and transmission characteristics of the transformer. The simulation results show that the flux leakage distribution of windings on each core column is mainly determined by the current flowing through these windings. The radial and axial acceleration distributions of the windings are U shape and M shape respectively along the winding height. The acceleration of B phase windings is smaller than that of A and C phase windings. The vibration of the oil tank surface is concentrated in its middle and lower part. The tank side vibration is mainly affected by the vibration of the nearest phase windings, while the tank front vibration is affected by the vibration of the three-phase windings together. This study is of great significance for further studies of the vibration characteristics of the transformer under unbalanced load and proposing the vibration reduction and noise reduction measures for the distribution transformer.